2014
DOI: 10.1257/pol.6.3.207
|View full text |Cite
|
Sign up to set email alerts
|

Under Pressure: Job Security, Resource Allocation, and Productivity in Schools under No Child Left Behind

Abstract: We conduct the first nationwide study of incentives under the No Child Left Behind (NCLB) Act, which requires states to punish schools failing to meet target passing rates on students' standardized exams. States' idiosyncratic policies created variation in the risk of failure among very similar schools in different states, which we use to identify effects of accountability pressure. We find NCLB lowers teachers' perceptions of job security, shifts time towards specialist teachers in high-stakes subjects and aw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 36 publications
2
58
1
Order By: Relevance
“…Research has found that scores rise more among students who are likely to determine their school's accountability (Reback, 2008), and test score gains from NCLB have been concentrated among students in the middle of the test score distribution (Neal & Schanzenbach, 2010). However, Reback et al (2014) found that students in a subgroup that placed their school in danger of failing AYP fared equally well in terms of test anxiety and "enjoyment" in math and reading as students outside that subgroup.…”
Section: Possible Differential Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has found that scores rise more among students who are likely to determine their school's accountability (Reback, 2008), and test score gains from NCLB have been concentrated among students in the middle of the test score distribution (Neal & Schanzenbach, 2010). However, Reback et al (2014) found that students in a subgroup that placed their school in danger of failing AYP fared equally well in terms of test anxiety and "enjoyment" in math and reading as students outside that subgroup.…”
Section: Possible Differential Effectsmentioning
confidence: 99%
“…Using selected items from the fifth-grade ECLS-K, the authors found a statistically significant decrease in the single item that measured test anxiety and no significant effect on indexes that they created of "enjoyment" of reading and math, with four items each, although point estimates are in a positive direction (Reback et al, 2014). 3 One other quasi-experimental study considers the effects of NCLB on socioemotional outcomes (Dee et al, 2013).…”
Section: Possible Positive Effectsmentioning
confidence: 99%
“…Building on the Dee and Jacob methodology, but with attention to the fidelity with which NCLB was implemented by individual states, Lee and Reaves () find no significant effects that can be attributed to the law on either overall achievement in reading or math or on achievement gaps. Using a very different approach that focuses on the pressure schools face when they are in danger of failing and measuring achievement by low stakes test results from national ECLS surveys rather than the NAEP, Reback, Rockoff, and Schwartz () find small positive effects in reading scores, but no statistically significant effects on math or science scores during the first 2 years of NCLB.…”
Section: Impact Of Nclb On Student Achievementmentioning
confidence: 99%
“…For example, the effort teachers and administrators exert might not be independent of the incentives they have (Friedman 1955;McMillan 2005;Reback et al 2014). Analogously, the organization of the school system itself might affect their decisions.…”
Section: Frameworkmentioning
confidence: 99%